Qualitative approach to determine competitiveness factors in craft breweries: evidence from Mexico - Cortina-Calderón, Karina Guadalupe; Delgado-Rivas, Jesús Gerardo; Ravina-Ripoll, Rafael; Galván Vela, Esthela (My University, 2024)
The craft beer industry is part of a sector that has experienced gradual growth in Mexico in recent years, thanks to the refinement of grape cultivation techniques and wine production. However, the literature has neglected how companies in this industry compete in this market. This study aims to identify factors that determine the competitiveness of the craft beer industry in Mexico. Qualitative research was carried out for this purpose using the grounded theory method. Ten owners of craft beer companies were interviewed using coding techniques and the constant comparison method, which involves identifying response patterns based on the frequency of mentions of an idea received during the interviews, in order to identify families and codes among the data. Among the results, a series of factors related to competitiveness in the sector were: quality, innovation, branding, strategic alliances between brewers, value-added sales and growing consumption trends. This study contributes to generating knowledge about competitiveness in the sector and joins the scarce literature on the subject.
International Journal of Management and Decision Making
Keywords: Competitiveness; Craft breweries; Beer; Qualitative approach; Grounded theory; Mexico; Campus Tijuana